Investigating approach/avoidance tendencies in male AUD patients through a gait initiation task: An exploratory posturography study - Salvatore Campanella; Macha Dubuson; Maylis Pereira; Harold Mouras; Guillaume Leonard; Xavier Noel; Thierry Lelard (PLoS ONE, 2025)
Introduction This exploratory study investigates approach/avoidance tendencies in male patients with Alcohol Use Disorder (AUD) through a gait initiation task combined with posturography. Method Seventy-four male participants (N = 74), including 47 AUD patients undergoing detoxification and 27 healthy controls, were exposed to alcohol-related, erotic, and neutral visual stimuli. Reaction times (RTs) and postural micromovements preceding gait initiation (forward/backward steps) were recorded to assess their predictive value for relapse (n = 13) or abstinence (n = 34) within two weeks post-detoxification. Results A mixed ANOVA (2x2x3) revealed significant group differences in RTs to alcohol-related stimuli (Stimuli × Group interaction: p = .029), with relapsers showing slower responses to alcohol cues than abstainers for forward as well as backward steps. Additionally, postural micromovements before gait initiation (measured through the standard deviation of the center of pressure’s position) showed a significant Stimuli × Group interaction (p = 0.05), with relapsers displaying increased micromovements when exposed to alcohol-related stimuli (p = .044). Conclusion These findings suggest that relapsers exhibited distinct motor responses to alcohol-related stimuli, characterized by delayed RTs and increased postural instability. These early indicators of relapse risk highlight the potential of posturography as a clinical tool in alcohol detoxification programs.